Statistical Cipher Feedback of Stream Ciphers. (13th July 2017) - Heys, Howard M
Abstract: In this paper, we examine a method of constructing a self-synchronizing stream cipher referred to as statistical cipher feedback (SCFB). Although recently studied as a mode for block ciphers, we explicitly consider the application of SCFB to hardware-oriented stream ciphers. Specifically, we show that SCFB can be used to realize a self-synchronizing stream cipher that has the characteristics of compact, efficient hardware implementations and is secure given that the underlying synchrononous stream cipher is secure. Further, we consider the communication properties of the SCFB system and examine the relationships between these properties and the implementation characteristics.